Stretching and exploiting thresholds for high-order war : how Russia, China, and Iran are eroding American influence using time-tested measures short of war - Connable, Ben (Research report (Rand Corporation), 2016)
"U.S. thresholds for high-order conventional and nuclear war are diffuse and dynamic, differ across regions, and are hard to enforce. Since 9/11, three of the primary nation-state competitors to the United States--Russia, China, and Iran--have successfully exploited or stretched U.S. thresholds for high-order war in order to further their strategic ends and, in the process, undermine U.S. interests. Each of these countries has made expert use of some combination of measures short of war, including economic leverage, terrorism, limited military incursions, aggressive diplomacy, and covert action, to enact its strategies. Some argue that these actions constitute a new international order, or perhaps a new way of war. They do not: Use of measures short of war is time-tested nation-state behavior. U.S. policymakers and military service leaders would benefit from additional consideration of these measures, how they are used against the United States, and how they might be defended against and exploited to further U.S. strategic interests"--Publisher's description.